The “Lieutenant Generation” and the Traditions of MGIMO-University - A. V. Shestopal (Vestnik MGIMO-Universiteta)
As a new age in the history of Russia was started by the events of 2014, we, the MGIMO alumni pondered deeply both upon the history of our country and upon the history of alma mater. Thus, we see the coincidence of MGIMO's 70th anniversary and of the 70th anniversary of the victory in the Great Patriotic War as far more meaningful than just a reason for formal celebration. The establishment of the groundwork of the MGIMO corporate ethic: exigency and amicability, proactiveness and responsibility, openness to the outside world and firmness in defending one's positions - is inseparably connected with the years of the "lieutenant generation", with its first enrollments and first graduations. The main accomplishments of the lieutenant generation of MGIMO graduates took place in 1950's-1970's, in the period of the development and realization of the policy of peaceful coexistence and detente. The policy of peaceful coexistence revealed in full measure both the pursuit of peace and the sober realism based upon the global balance of power. The idea of peaceful coexistence may well be seen as a prototype of the concept of a polycentric world, formulated by the successors of the lieutenant generation at the turn of the XXI century. Hard times did not pass MGIMO by. Fortunately, though, among the merits of the lieutenant generation was the merit of bringing up another MGIMO generation, which preserved the school during the turmoil of the 1990's. In the 1990's-2000's drawing upon its initial traditions, MGIMO became a full-fledged university with manifold international ties both in the West and in the East. Studies dedicated to the Great Patriotic war occupy a particular place in the research activities of MGIMO scholars. These studies have not only historical but also a great educational value, drawing a wide student response and inspiring youth to engage in cross-generation dialogue.